2018
DOI: 10.1016/j.neubiorev.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Theory of Mind profiles of patients with anorexia nervosa and individuals on the autism spectrum: A meta-analytic review

Abstract: Although both people with AN and autistic people have significant difficulties in all aspects of theory of mind relative to the HCs, some differences in the underlying profile may be present. However, due to relative paucity of theory of mind research among people with AN, further research is still needed before firm conclusion can be drawn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 142 publications
3
68
1
1
Order By: Relevance
“…Potential mechanisms underlying the relationship between AN and autism could include shared cognitive traits: commonly with research in autism, literature shows that people with AN exhibit problems with rigidity, central coherence, and emotional and social processing that may persist following recovery (Harrison, Mountford, & Tchanturia, 2014;Lang, Lopez, Stahl, Tchanturia, & Treasure, 2014;Katie Lang et al, 2016;Leppanen, Sedgewick, Treasure, & Tchanturia, 2018;Westwood, Lawrence, Fleming, & Tchanturia, 2016;Westwood, Stahl, Mandy, & Tchanturia, 2016). Significantly, heightened autistic traits in people with AN are associated with more severe presentations and poorer treatment outcomes (Nielsen, Anckarsater, Gillberg, Rastam, & Wentz, 2015;Tchanturia, Adamson, Leppanen, & Westwood, 2017;Tchanturia, Larsson, & Adamson, 2016), leading to suggestions that traditional treatment approaches may need to be adapted for this population (Dudova, Kocourkova, & Koutek, 2015;Stewart, McEwen, Konstantellou, Eisler, & Simic, 2017;.…”
Section: Introductionmentioning
confidence: 99%
“…Potential mechanisms underlying the relationship between AN and autism could include shared cognitive traits: commonly with research in autism, literature shows that people with AN exhibit problems with rigidity, central coherence, and emotional and social processing that may persist following recovery (Harrison, Mountford, & Tchanturia, 2014;Lang, Lopez, Stahl, Tchanturia, & Treasure, 2014;Katie Lang et al, 2016;Leppanen, Sedgewick, Treasure, & Tchanturia, 2018;Westwood, Lawrence, Fleming, & Tchanturia, 2016;Westwood, Stahl, Mandy, & Tchanturia, 2016). Significantly, heightened autistic traits in people with AN are associated with more severe presentations and poorer treatment outcomes (Nielsen, Anckarsater, Gillberg, Rastam, & Wentz, 2015;Tchanturia, Adamson, Leppanen, & Westwood, 2017;Tchanturia, Larsson, & Adamson, 2016), leading to suggestions that traditional treatment approaches may need to be adapted for this population (Dudova, Kocourkova, & Koutek, 2015;Stewart, McEwen, Konstantellou, Eisler, & Simic, 2017;.…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence suggest that social‐affective difficulties, when present in individuals with AN, may differ from those documented in individuals with autism (Leppanen, Sedgewick, Treasure, & Tchanturia, 2018). This finding supports the possibility that a different set of ADOS‐2 items than those forming the existing algorithm might be better suited to describe these difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…First, inefficiencies of social perception and Theory of Mind tend to be elevated among adults, but not in adolescents with AN (Caglar‐Nazali et al, 2014; Leppanen et al, 2018). Second, a meta‐analytic review found that individuals with AN and individuals with autism exhibit different profiles of difficulties with Theory of Mind (Leppanen et al, 2018). Third, using the ADOS‐2, a study found a significant difference between adolescents with AN and HCs on three ADOS‐2 items, which are not part of the existing algorithm (the items ‘Offers information’, ‘Reporting of events’, and ‘Amount of Social Overtures’; Bentz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there is an increasing interest in exploring characteristics associated with autism that may play a role in maintenance models of AN, contributing to these poorer outcomes. For example, previous studies have investigated similarities in cognitive rigidity and theory of mind difficulties in AN and autism, both of which are thought to act as potential perpetuating factors in the illness [8][9][10]. To date, there is less research on the implications of sensory sensitivity in autism for AN.…”
Section: Introductionmentioning
confidence: 99%